PENGARUH HARGA DAN PROMOSI TERHADAP MINAT BELI PADA DIA DAN KOPI DI KOTA TANGERANG - Dede Solihin; Fikri Bachrul Anam Azka (Journal of Research and Publication Innovation, 2024)
The purpose of the research was conducted to determine the effect of price and promotion on buying interest in Dia Dan Kopi in Tangerang City. This study uses quantitative methods with descriptive and verification research types. The population in this study amounted to 1,975 people, the sampling technique used the slovin formula and obtained 95 respondents who were sampled with data collection techniques using a questionnaire or questionnaire. The analysis techniques in this study are descriptive analysis, research instrument test, classical assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, t test and F test using SPSS version 26. The results of this study indicate that price (X1) has a positive effect on purchase intention (Y) at Dia Dan Kopi in Tangerang City, indicated by the results of the t test obtained tcount > ttable or (4.674> 1.985) This is also reinforced by the value of ρ value < Sig.0.05 or (0.000 < 0.05). or (0.000 < 0.05), then H01 is rejected and Ha1 is accepted, meaning that there is a significant influence between price (X1) on purchase intention (Y), secondly promotion (X2) has a positive effect on purchase intention (Y) at Dia Dan Kopi in Tangerang City, indicated by the t test results obtained tcount > ttable or (5.327> 1.985) This is also reinforced by the ρ value < Sig.0.05 or (0.000 <0.05), then H02 is rejected and Ha2 is accepted, meaning that there is a significant influence between promotion on purchase intention, and the three prices (X1) and promotion (X2) have a positive effect on purchase intention (Y) at Dia Dan Kopi in Tangerang City, indicated by the results of the fcount value of 18.059 with ftabel 3, 095 so that the value of fcount = 18.059 > ftabel = 3.095 has a probability value of sig 0.000 <0.05, then Ha3 is accepted and rejects Ho3 it can be concluded that the two independent and dependent variables together have an effect, namely price and promotion have a significant and simultaneous effect on buying interest.